An extractive membrane biofilm reactor as alternative technology for the treatment of methyl tert‐butyl ether contaminated water. (23rd June 2016) - Guisado, I. M.; Purswani, J.; González‐López, J.; Pozo, C.
Abstract : Among the strategies developed for contaminated groundwater bioremediation, those based on the use of bacteria adhering to inert supports and establishing biofilms have gained great importance in this field. Extractive membrane biofilm reactor (EMBFR) technology offers productive solutions for the removal of volatile and semi‐volatile compounds. EMBFR technology is based on the use of extractive semipermeable membranes through which contaminants migrate to the biological compartment in which microorganisms with pollutant biotransformation and/or mineralization capacities can grow, forming an active biofilm on the membrane surface. The objective of this study was to assess the use of three bacterial strains ( Paenibacillus sp. SH7 CECT 8558, Agrobacterium sp. MS2 CECT 8557, and Rhodococcus ruber EE6 CECT 8612), as inoculum in a lab‐scale EMBFR running for 28 days under aerobic conditions to eliminate methyl tert ‐butyl ether (MTBE) from water samples. Three different hydraulic retention times (1, 6, and 12 h) were employed. MTBE degradation values were determined daily by a gas GC‐MS technique, as well as suspended bacterial growth. The biofilm established by the bacterial strains on the semipermeable membrane was detected by Field‐Emission Scanning Electron Microscopy (FESEM) at the end of each experiment. The acute toxicity of the treated effluents and biomedium was determined by Microtox © assay (EC50 ).The results achieved from the MTBE degradation, biofilm formation, and toxicity analysis indicated that bacterial strains MS2 and EE6 were the best options as selective inoculum, although further research is needed, particularly with regard to their possible use as a mixed culture. © 2016 American Institute of Chemical Engineers Biotechnol. Prog ., 32:1238–1245, 2016